Impact of Diagenesis on the isotope signature of Cretaceous Sponge Spicules from the DSDP Leg 79 Site 545 - Franziska Maria Stamm; Rebecca A Pickering; Patrick J Frings; Daniel A Frick; Sylvain Richoz; Daniel J Conley (PANGAEA, 2024)
Cretaceous siliceous sponge spicules spanning from late Aptian (~ 116-113 Ma) to middle Albian (~109-105 Ma) collected from DSDP Leg 79 Site 545 exhibited two preservation states: visually similar to modern (category 1), or clearly altered towards a milky, translucent composition (category 2). A suite of geochemical and structural analyses (XRD, Raman spectroscopy and FT-IR spectroscopy) was applied to investigate and compare strucutral and chemical changes. The effect of (early) diagenesis on isotope signatures was studied by comparing MC-ICP-MS and SIMS δ30Si and δ18O values of spicules from both categories within single samples.